KEANAKARAGAMAN JENIS DAN PENYEBARAN MAMALIA DI KAMPUS IPB DRAMAGA BOGOR - Abdul Haris Mustari; Indra Zulkarnain; Dones Rinaldi (Media Konservasi, 2014)
This study aimed to reveal mammals species, distribution and diversity of mammals in campus area of IPB at Dramaga. The mammals species data was collected using strip transect, life trap, and concentration count methods. As many as 11 families and 6 ordos of mammals consisting of 14 species were recorded in this study. Javan treeshrew (Tupaia javanica), malaysian wood rat (Rattus tiomanicus jalorensis), and plantain squirrel (Callosciurus notatus) were the most widely distributed mammals based on Margalef Index scoring 1.44. Serious threats for mammals on IPB Dramaga campus area are illegal hunting, area constringency, and habitat devastation as impact of the campus development. Thus, it needs conservation area for wildlife including mammals on IPB Dramaga campus and also support from campus and community for wildlife conservation. Key words: Distribution, Diversity, Mammals